Assessing the mediating effect of digital innovation on the relationship between digital leadership and business performance: The case of District Sports Center - Bartlett, Jordan Mejica (Animo Repository, 2022)
The aim of this research was to determine the mediating effect emanating from digital innovation vis-à-vis the influence of digital leadership onto business performance in District Sports Center. Guided primarily by the digital innovation theory and dynamic capabilities theory, the research addressed the gap of the impact emanating from digital leadership in influencing digital innovation and subsequently business performance within the fitness industry. This study made use of a descriptive, correlational, causal-explanatory, and case study research design as well as a critical case sampling design. It used a survey questionnaire to gather the necessary data from the employees of the District Sports Center in order to gain more information about the company’s digital leadership, digital innovation, and business performance. A pre-test was done on the survey to ensure its consistency and reliability before releasing it for actual data collection. The research was able to gather 46 valid respondents in relation to the study. Using both descriptive and inferential statistics, the study arrived at the conclusion that digital innovation indeed had a statistically significant and had a full mediating effect onto the influence of digital leadership on business performance. Given this, the study provided recommendations to management that their digital leadership should be focused on adapting onto the new innovations vis-à-vis fitness industry so as to help improve their business performance at large. Some suggestions for academe and future researchers were also provided to determine areas which may be pursued in future studies.